Racun Tiktok: Inspirasi Facecare di Kalangan Mahasiswi Kota Makassar - Dhea Sari Ramadhian Abdullah (Emik, 2023)
Technological developments have made the world more borderless, information easier to obtain and in a short time, one of the information media is social media, including TikTok which is booming and provides a lot of information, including information about facecare. Recently, TikTok has become one of the most popular social media which displays not only facecare products, but also tips to contend with facecare. Using qualitative approach, this research was conducted in the city of Makassar. There are ten female students participated in this study, whose age ranging between 18 and 22 years old and who regularly use TikTok application and perform facecare. Data was collected using the combination of indepth interview and observation. The study shows that for female students, facecare is a series of activities that use a variety of products to maintain healthy faceskin and to deal with faceskin problems, so that it looks â€œglowingâ€ (white, shining, smooth textured, and tight), like the skin of Korean artists which reflects the ideal Indonesian women's skin today. Even though there are lots of content presenting facecare products on TikTok, to choose a product, female students first understand their skin type, the variety of facecare products, look for products that are suitable for their skin type. Skin types vary from normal skin, oily skin, combination skin, or sensitive skin. In terms of product variety, facecare consists of two, namely: basic products and advanced products with their respective functions. While the former includes products for cleansing, toning, moisturizing, protecting, eye creaming, the latter consists of masking, seruming, essence, ampouling (ampoules), and acne spotting (acne spots) for those with acne. Uniquely, the facecare products used are not well-known brand facecare products, but new brand products that are popularized by TikTok. Meanwhile, they use trial and error method to find a product that suits their skin. Information and references from TikTok are taken into consideration in choosing facecare products. Female students use social media TikTok as a source of information for facecare because TikTok provides facecare content, because TikTok has reviews of facecare products, and because of peer influence. It is argued in this article that even though TikTok has become a source of information for facecare, the selection of facecare products is highly dependent on the compatibility of one's facial skin.